Jawabanmu

2014-01-18T15:30:46+07:00
2x + 4y + 2  = 0      x3
3x - y -11=0            x2        -
----------------------------------------------
6x + 12 y + 6 = 0
6x - 2y - 22 = 0                -
----------------------------------------------
14 y + 28 = 0
y = 28/14 = 2



2x + 4y + 2  = 0     
3x - y -11=0             +        x4
-------------------------------------------------
2x + 4y + 2 = 0
12x - 4y-44 = 0             +
------------------------------------------
14 x - 42 = 0
x = -42/14
x = -3